CUMHURİYETİN İLK YILLARINDA LÜLE TAŞI MADENCİLİĞİ - Turp, Muharrem (TURAN : stratejik arastirmalar merkezi, 2025)
Due to its structure, meerschaum is a mineral that can be easily carved and shaped into various shapes. Therefore, it has a very wide area of use. However, However, meerschaum was mostly used in making pipes, prayer beads, figurines and ornaments. Eskişehir ranks first in the world in terms of meerschaum reserves. During the time of the Ottoman State, meerschaum -extracted from Eskişehir- was exported to various countries, especially Austria. Its use in pipe making in particular, increased the demand for meerschaum along with the increase in tobacco use. Although the Ottoman State aimed to earn significant income through meerschaum exports, demand for meerschaum began to decrease, primarily with the impact of wars. Various initiatives were taken to increase meerschaum production and export since the early years of the Republic. During this period, the Eskişehir Meerschaum Mine Turkish Joint Stock Company and the Eskişehir Meerschaum Miners and Processors Cooperative were established, and articles were published in the press on how to increase interest in meerschaum. These developments are important in terms of showing the importance that the Republican administration attached to meerschaum.